Combining mental health and climate-smart agricultural interventions to improve food security in humanitarian settings: study protocol for the THRIVE cluster-randomized controlled trial with mothers in Nakivale refugee settlement, Uganda - Hall, Jonathan; Ainamani, Herbert E.; Vassiliou, Phaidon T. B.; Döring, Stefan; Gredebäck, Gustaf; Peltonen, Kirsi; Scharpf, Florian; Sen, Umay; Sutter, Matthias; Walsh, James I.; Hecker, Tobias (BioMed Central, 2026)
Background
Climate extremes in Africa threaten the food security of war-affected refugees, who often experience mental health challenges that hinder their capacity for agricultural adaptation. Cost-effective, climate-smart farming interventions are crucial for addressing food insecurity in humanitarian contexts, yet evidence on their effectiveness is limited, and the potential benefits of integrating them with mental health interventions remain unexplored. We hypothesize that the success of agricultural interventions, especially under adversity, is influenced by mental health and psychological functioning.
Methods
This study employs a three-arm, parallel-group, cluster-randomized controlled trial (cRCT) in the Nakivale refugee settlement, Uganda. Thirty villages within the settlement will be randomized in a 1:1:1 allocation ratio to one of three conditions: Enhanced Usual Care, a Home Gardening Intervention (HGI) or HGI combined with the peer-delivered psychosocial intervention Self-Help Plus (SH + HGI). A total of 900 refugee mothers and their children (aged 3–4 years) will be enrolled, with 30 dyads per village. The primary outcome is food insecurity at 12 months post-intervention, assessed using the Food Insecurity Experience Scale (FIES). Secondary outcomes include dietary diversity, child malnutrition and mothers’ psychological distress. Data will be collected at baseline, 3-month and 12-month follow-ups. Primary analyses will use an intention-to-treat (ITT) approach.
Discussion
This study will shed light on the role of mental health in agricultural adaptation for food security, evaluating the efficacy of scalable, cost-effective interventions in a refugee setting. The findings will have implications for the design and implementation of integrated food security and mental health programs in humanitarian and other resource-constrained settings.